2008
DOI: 10.1002/bies.20731
|View full text |Cite
|
Sign up to set email alerts
|

Silicon nanotechnologies of pigmented heterokonts

Abstract: Many pigmented heterokonts are able to synthesize elements of their cell walls (the frustules) of dense biogenic silica. These include diatom algae, which occupy a significant place in the biosphere. The siliceous frustules of diatoms have species-specific patterns of surface structures between 10 and a few hundred nanometers. The present review considers possible mechanisms of uptake of silicic acid from the aquatic environment, its transport across the plasmalemma, and intracellular transport and deposition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 63 publications
2
27
0
1
Order By: Relevance
“…The calculated SDV volumes to enable silica polymerization to form the new hypovalve are as expected; they agree well with the observed pale fluorescent vesicles that are observed in studying valve morphogenesis [19,31,40]. If simultaneously water is expelled [20,35] the SDV constituents concentrate, allowing silicic acid to polymerize when the proper saturation level has been reached [14,15]. This concentration is supported by the intensity change of the compound used in fluorescent probing [40] while at the same time the shape of the SDV, and potentially its volume, changes upon compression towards the cleavage furrow [16,17,19,31].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The calculated SDV volumes to enable silica polymerization to form the new hypovalve are as expected; they agree well with the observed pale fluorescent vesicles that are observed in studying valve morphogenesis [19,31,40]. If simultaneously water is expelled [20,35] the SDV constituents concentrate, allowing silicic acid to polymerize when the proper saturation level has been reached [14,15]. This concentration is supported by the intensity change of the compound used in fluorescent probing [40] while at the same time the shape of the SDV, and potentially its volume, changes upon compression towards the cleavage furrow [16,17,19,31].…”
Section: Discussionsupporting
confidence: 85%
“…The results prompted us to further focus on macropinocytosis-mediated Si uptake ( If this mechanism is applicable, the larger vesicle formed intracellularly subsequently may be compressed towards the cleavage furrow by cellular and membrane activity [16,17,22,23]; especially when simultaneously water is expelled [20,35] the concentration of silicic acid to the threshold for autopolymerization would be achieved [14,15]. For T. pseudonana it is demonstrated that silica is formed in the most compressed region of the SDV [16].…”
Section: Mathematical Assessment Of Alternative Silicic Uptake Modelsmentioning
confidence: 99%
“…Consequently the process of syneresis in sponges is a subsequent step, following silicateinmediated formation of the primary biosilica product and preceding the final step of biosintering under formation of the compact biosilica rods, the spicules. By focusing on biosilica formation in organisms other than sponges, such as diatoms, the relevance of the process of syneresis has been stressed theoretically, [37] but to the best of our knowledge, not yet experimentally approached. The data presented, using the sponge model, might also be relevant for the possible application of biosilica in the fields of biophotonics, photoluminescence, and microfluidics for generating multiscale porous materials, as summarized.…”
Section: Discussionmentioning
confidence: 99%
“…약 2 µm~2 mm의 다 양한 크기로 분포하는 규조류는 공통적으로 단단한 다공성 실리카 (silica)벽을 갖는 단일 세포이며 각각 종의 독특한 껍 질 형태에 따라 분리하였을 때 약 10만종 이상이 존재하는 것으로 추정된다 [1,2]. 규조류에 대한 분류는 아직 완전히 정립되지 않았지만 형태에 따라 크게 2가지의 분류가 적용 되고 있다.…”
Section: 규조류의 구조적 다양성 규조류는 전체 지구 생물 종 중에서 총 유기물 생산량의 25%unclassified